Carbon Isotope Chemostratigraphy Across the Permian-Triassic Boundary at Chaotian, China: Implications for the Global Methane Cycle in the Aftermath of the Extinction - Saitoh, Masafumi; Isozaki, Yukio (Frontiers in Earth Science, 2021)
During the end-Permian extinction, a substantial amount of methane (CH4) was likely released into the ocean-atmosphere system associated with the Siberian Traps volcanism, although fluctuations in the global CH4 cycle in the aftermath of the extinction remain poorly understood. The carbon (C) isotopic composition of carbonate (δ13Ccarb) across the Permian-Triassic boundary (P-TB) was analyzed at Chaotian, South China. The δ13Ccarb values decrease from ca. +1 to –2‰ across the P-TB, possibly caused by a collapse of primary productivity associated with the shallow-marine extinction. The frequent intercalation of felsic tuff layers around the P-TB suggests that a volcanogenic carbon dioxide (CO2) input to the surface oceans may also have contributed to the δ13Ccarb decline. The magnitude of the δ13Ccarb decrease (∼3‰) is substantially smaller than the magnitude of a decrease in C isotopic composition of organic matter (δ13Corg) in the same P-TB interval (∼7‰). This apparent δ13Ccarb-δ13Corg decoupling could be explained by proliferation of methanogen (“methanogenic burst”) in the sediments. A global δ13C compilation shows a large variation in marine δ13Corg records, implying that the “methanogenic burst” according to the Siberian Traps volcanism may have contributed, at least in part, to the δ13Corg variability and to the elevated CH4 levels in the atmosphere. The present and previous observations allow us to infer that the global CH4 cycle may have fluctuated substantially in the aftermath of the extinction.